Pancreas Fat, an Early Marker of Metabolic Risk? A Magnetic Resonance Study of Chinese and Caucasian Women: TOFI_Asia Study - Sequeira, Ivana R.; Yip, Wilson C.; Lu, Louise W. W.; Jiang, Yannan; Murphy, Rinki; Plank, Lindsay D.; Cooper, Garth J. S.; Peters, Carl N.; Lu, Jun; Hollingsworth, Kieren G.; Poppitt, Sally D. (Frontiers in Physiology, 2022)
OBJECTIVE: Susceptibility to type 2 diabetes (T2D) is hypothesised due to organ fat accumulation. Impact on early risk, particularly in thin-on-the-outside-fat-on-the-inside (TOFI) individuals, is undetermined. METHODS: Multivariate regressions identified relationships between abdominal ectopic fat; using magnetic resonance imaging and spectroscopy, in 68 lean and overweight, normo- and dysglycaemic women with fasting plasma glucose (FPG) and insulin resistance (HOMA2-IR) from the cross-sectional TOFI_Asia study. RESULTS: Chinese women were younger with lower bodyweight but similar BMI and %total body fat (TBF) than Caucasians. HDL-C, total- and high-molecular weight adiponectin were significantly lower, while GLP-1 and glucagon significantly higher in Chinese. There were no ethnic differences between %pancreas fat and %liver fat. At low BMI, %pancreas and %liver fat was 1% and 2% higher in Chinese. In all, %pancreas and visceral adipose tissue had strongest correlation with FPG independent of age and %TBF. %pancreas fat and age positively contributed to variance in FPG, whereas %TBF, amylin and C-peptide contributed to IR which was 0.3 units higher in Chinese. CONCLUSIONS: Pancreas fat accumulation may be an early adverse event, in TOFI individuals, with peptides highlighting pancreatic dysfunction as drivers of T2D susceptibility. Follow-up is warranted to confirm causality.